Analyzing Filial Loyalty in Anita Desai’s “A Devoted Son” - Humagain, Abhimanyu (International Research Journal of MMC, 2026)
Filial loyalty is central to comprehending parent-child relationships in contemporary Indian family narratives. The objective of the study is to analyze filial loyalty in the story “A Devoted Son” by Anita Desain. It adopted a qualitative textual analysis research design in which the primary data were drawn from selected excerpts of the story, while secondary data were collected from relevant books and journal articles. A comprehensive review of secondary data was conducted to support and contextualize the findings. Thematic analysis was applied to analyze the excerpts as data and identify patterns in the depiction of filial loyalty. The findings revealed Rakesh’s unwavering filial loyalty as one of the most prominent themes in the story. This study suggests that filial relationships in literature can provide insights into cultural expectations and emotional dynamics within families.